Analysis of Management Functions in the Development of Guidance and Counseling Service Materials - Muhtadi, Hasna Fathinah; Suherman, Uman (Buletin Konseling Inovatif, 2025)
The management function in guidance and counseling must be carried out carefully, including in the development of guidance and counseling materials for students. The aim of this research is to provide an overview of the management function in developing guidance and counseling materials in one of the schools in Tasikmalaya, Indonesia. This research is qualitative in nature, the respondents of this research are school counselors in junior high school and vocational high schools with a case study design, data collection through semi-structured interviews and data analysis in the form of data reduction, data presentation and drawing conclusions. The results of this research indicate that the application of management functions in the development of guidance and counseling materials is very important to ensure the effectiveness of guidance and counseling programs in schools. The challenges felt by respondents were limited facilities, time allocation and varying roles between teaching other subjects and guidance and counseling. The implementation of management functions cannot be separated from the support and involvement of school officials, so that in overcoming these challenges, support from school officials is considered important in providing guidance and counseling materials.